Pengaruh Suku Bunga Acuan dan Nilai Kurs Tengah Valuta Asing Terhadap Return Saham - Ivan Pratama; Lauw Tjun Tjun (Jurnal Akuntansi, 2017)
AbstractInflation is one of the phenomena that indicate a monetary policy is not effective or monetary crisis is going on. It can stimulate weak of the exchange rate, declining purchasing power, as well as fluctuations in interest rate (BI Rate) which make the performance of the company may face a problem that will have an impact on the development of capital markets. Companies with good performance can attract more investors. The purpose of this research is to determine the effect of interest rate (BI Rate) and foreign exchange currency (USR-IDR) Bank of Indonesia to stock returns. The sample selection using purposive sampling technique. The samples are banking companies list on Indonesia Stock Exchange in 2012-2015 with some criteria. This research uses secondary data from Bank of Indonesia data reports in 2012-2015 and banking companies stock price reportin 2012-2015. The analysis model is multiple linear regression with help from SPSS and the significance level is 0.05. Results of this research is that interest rate (BI Rate) and foreign exchange currency (USR-IDR) Bank of Indonesia simultaneous effect on stock returns with effect level of 8.6% and a significance value of 0.029. But partially, they have no effect on stock returns.Keywords: Â  Interest Rate (BI Rate), Foreign Exchange Currency (USD-IDR), and Stock Return.Â